Ductal stenting vs. surgical shunting in late presenting duct-dependent pulmonary circulation: a single-center experience - Prakoso, Radityo; Simanjorang, Christine Nathalina Sinaga; Kurniawati, Yovi; Mendel, Brian; Rahmat, Budi; Zahara, Rita; Rudiktyo, Estu; Sakti, Damba Dwisepto Aulia; Sukmawan, Renan (Frontiers in Cardiovascular Medicine, 2024)
Background PDA stenting is an option to mBTT shunt for younger patients; nevertheless, few reports of this palliative approach have been made for the late presenter population, especially for patients who are older than 30 days but under 5 years. This study aimed to evaluate the clinical result and intra-hospital costs of ductal stenting in late-presenting patients in comparison to surgical shunting.Methods A single-center, retrospective cohort study was conducted from August 2016 to August 2022. This study included patients with pulmonary duct dependent CHD who were hospitalized for palliative therapy. The extracted data were baseline characteristics, clinical findings, supportive examination findings, complications, outcomes, and length of stay of the patients. Monitoring was carried out during treatment up to 30 days after the procedure.Results A total of 143 patients were included in the analysis; 43 patients underwent PDA stent and 100 patients underwent mBTT shunt with median age of PDA stent group 110 (31-1498) days and mBTT shunt group 174.5 (30-1651) days. Primary outcome composite was not significant in both groups including 30 days mortality (6(14%) vs 14(14%), p=1.000), reintervention (1(2.3%) vs 7(7%),p=0.436), and 30 days rehospitalization (0(0%) vs 2(2%), p=0.319). Secondary outcome analysis showed shorter ICU length of stay in the PDA stent group (2 (0-16) days vs 4 (1-63) days, p = 0.002).Conclusions PDA stent has an outcome that is non inferior from the mBTT shunt procedure in the composite outcome including 30 days mortality, reintervention, and 30 days rehospitalization but significantly lower in ICU length of stay.